Water loss through evapotranspiration after precipitation events in bioenergy crops grown in similar climatic conditions - Postma, Kevin; Mane, Siddhesh; Shen, Meicheng; Kussainova, Maira; Beisenova, Raikhan; Nanda, Arunav; Dong, Gang; Chen, Jiquan (Frontiers in Environmental Science, 2024)
The relationship between precipitation and evapotranspiration (ET) is critical to understanding water cycle and dynamics in ecosystems, including crops. Existing studies of bioenergy crops have primarily focused on annual or seasonal ET rates, with less attention to the immediate ET response following precipitation events. This study examines the variation in ET rates in the days subsequent to precipitation events across various bioenergy crops-corn, switchgrass, and prairies-utilizing thirteen years (2010-2022) of growing season data. Meteorological and eddy covariance flux data were collected from seven eddy-covariance flux towers as part of the GLBRC scale-up experiment at the Kellogg Biological Station Long Term Ecological Research sites. The analysis revealed that average ET peaked the day after precipitation and declined linearly over the following days, with a statistically significant relationship (p-value = 0.00027, R² = 0.96). Neither the type of biofuel vegetation nor the historical land use significantly influenced ET postprecipitation events (p-values = 0.53 and 0.153, respectively). Key predictors of ET following precipitation events include shortwave radiation, seasonal variation, day of the year, ambient temperature, vapor pressure deficit (VPD), long-wave radiation, precipitation amount, soil moisture, and annual variability. These findings enhance our comprehension of ET responses in bioenergy crop systems, with implications for water management in sustainable agriculture.